Differential antagonism by conotoxin p-TIA of contractions mediated by distinct alpha(1)-adrenoceptor subtypes in rat vas deferens, spleen and aorta - Lima, V; Mueller, A.; Kamikihara, S. Y.; Raymundi, V; Alewood, D.; Lewis, R. J.; Chen, Z. J.; Minneman, K. P.; Pupo, A. S. (Elsevier B.V., 2005)
The ability of the conotoxin p-TIA, a 19-amino acid peptide isolated from the marine snail Conus tulipa, to antagonize contractions induced by noradrenaline through activation of alpha(1A)-adrenoceptors in rat vas deferens, alpha(1B)-adrenoceptors in rat spleen and alpha(ID)-adrenoceptors in rat aorta, and to inhibit the binding of [I-125]HEAT (2-[[beta-(4-hydroxyphenyl)ethyl]aminomethyl]-1-tetralone) to membranes of human embryonic kidney (HEK) 293 cells expressing each of the recombinant rat alpha(1)-adrenoceptors was investigated. p-TIA (100 nM to 1 muM) antagonized the contractions of vas deferens and aorta in response to noradrenaline without affecting maximal effects and with similar potencies (pA(2)similar to7.2, n=4). This suggests that p-TIA is a competitive antagonist of alpha(1A)- and alpha(1D)-adrenoceptors with no selectivity between these subtypes. Incubation of p-TIA (30 to 300 nM) with rat spleen caused a significant reduction of the maximal response to noradrenaline, suggesting that p-TIA is a non-competitive antagonist at alpha(1B)-adrenoceptors. After receptor inactivation with phenoxybenzamine, the potency of p-TIA in inhibiting contractions was examined with similar occupancies (similar to25%) at each subtype. Its potency (pIC(50)) was 12 times higher in spleen (8.3 +/- 0.1, n=4) than in vas deferens (7.2 +/- 0.1, n=4) or aorta (7.2 0.1, n=4). In radioligand binding assays, p-TIA decreased the number of binding sites (B,,,,,,) in membranes from HEK293 cells expressing the rat alpha(1B)-adrenoceptors without affecting affinity (K-D), In contrast, in HEK293 cells expressing rat alpha(1A)- or alpha(1D)-adrenoceptors, p-TTA decreased the KD without affecting the B-max. It is concluded that p-TIA will be useful for distinguishing the role of particular alpha(1)-adrenoceptor subtypes in native tissues. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: alpha(1)-adrenoceptor; conotoxin p-TIA; vas deferens; spleen; aorta